Control of Lymantria dispar L. for eliminating the risk of forage production loss for small ruminants - Papadopoulou S.; Chryssochoides C.; Katanos J. (Nutritional and foraging ecology of sheep and goats, 2009)
Range plants that constitute the basic feed source for grazing animals are harmed due to various biological and environmental factors. The quality and quantity of kermes oak (Quercus coccifera L.), mostly preferred by small ruminants (goats) because of the high ratio of sugar to tannin content in its leaves, can be affected seriously by infestation by gipsy moth (Lymantria dispar L.). In securing the quantity and protecting the quality of kermes oak vegetation, an experiment was designed to address the gipsy moth problem. During spring 2006, 2nd instar larvae were collected from the watershed of the Migdonia area of Thessaloniki prefecture and put in cases where insecticides were applied. At the same time, the entomopathogenic nematode, Steinernema carpocapsae, which was applied for first time in Greece as a biological control against gipsy moth, was also tested. Five treatments in four replications were applied. The results from the experiment demonstrated that S. carpocapsae can be used successfully as a biological control agent against gipsy moth larvae.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)